Tata Kelola Madrasah Tsanawiyah Kabupaten Lima Puluh Kota - Suardi Suardi; Junaidi Junaidi; Yelfi Dewi; M. Arif (Journal on Education, 2023)
The purpose of this research is to clearly describe how governance is carried out by madrasahs accredited A, B, and C in Fifty Cities District.This type of research is qualitative with descriptive analysis. This research was conducted at Madrasah Tsanawiyah with A accreditation, Madrasahs with B accreditation, Madrasahs with C accreditation. Data collection procedures are carried out by field research, interviews, and documentation. Data analysis procedures were carried out by reducing data, presenting data, and drawing conclusions.From the research that has been conducted, information is obtained that madrasahs with A accreditation perform good governance starting from planning by holding end-of-semester meetings to prepare for the next semester, developing local content curricula, managing students in the form of PPDB, extracurricular activities, setting student rules, determining graduation. , from the point of view of educators and education staff, there are already masters graduates. Funding for education comes from several sources such as from BOS, infaq, committees and these funds are allocated as best as possible for the benefit of the madrasah. Madrasan also establishes relationships with the community by making MoUs with the police, village guardians, sub-district heads, health centers, and course institutions. Madrasahs with B accreditation have implemented good governance such as developing local content curricula, student activities such as PPDB, extracurricular activities, making student rules, madrasah funds obtained from BOS, and also establishing relationships with the community such as the police and puskesmas. All of these activities were well planned but there were still some that were not implemented. Madrasahs with accreditation C, all of which are private Madrasah Tsanawiyah with not too many students, have already carried out planning by the madrasa such as curriculum development, implementing student admissions, funds coming from foundations or alumni, and not collecting funds from students.